Co‐optimisation and settlement of power‐gas coupled system in day‐ahead market under multiple uncertainties. Issue 8 (20th April 2021) - Zheng, Xiaodong; Xu, Yan; Li, Zhengmao; Chen, Haoyong
Abstract: The interdependency of power systems and natural gas systems is being reinforced by the emerging power‐to‐gas facilities (PtGs), and the existing gas‐fired generators. To jointly improve the efficiency and security under diverse uncertainties from renewable energy resources and load demands, it is essential to co‐optimise these two energy systems for day‐ahead market clearance. A data‐driven integrated electricity‐gas system stochastic co‐optimisation model is proposed in tis work. The model is accurately approximated by sequential mixed integer second‐order cone programming, which can then be solved in parallel and decentralised manners by leveraging generalised Benders decomposition. Since the price formation and settlement issues have rarely been investigated for integrated electricity–gas systems in an uncertainty setting, a novel concept of expected locational marginal value is proposed to credit the flexibility of PtGs that helps hedging uncertainties. By comparing with a deterministic model and a distributionally robust model, the advantage of the proposed stochastic model and the efficiency of the proposed solution method are validated. Detailed results of pricing and settlement for PtGs are presented, showing that the expected locational marginal value can fairly credit the contribution of PtGs and reflect the system deficiency of capturing uncertainties.